Primeiro como lei, depois como farsa: do estado de direito aos direitos humanos a partir de Slavoj Zizek - Xavier, Bruno Gadelha (2016)
The main objective of this dissertation is a philosophical and political discussion about the elements Democratic Rule of Law, the Subject of Law and Human Rights, from a reding of Slavoj Zizek’s work . The author points out the existence of numerous ideological factors that sustain social practices and political institutions, his analysis also gives possibilities of study on the relationship between Rule of Law and market circulation to take based on a Hegelian tradition together with Lacanian psychoanalysis . Therefore, this writing will develop an approach on the relationship between State and merchandise from an ideological context, and also work with the subjectivity of "Post-Traumatic Subject" . Nevertheless, it will consider the context of Human Rights and Multiculturalism , taking the last element as a form of cultural racism.